2010
DOI: 10.1161/atvbaha.109.200683
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Novel Interaction Between Vasodilator-Stimulated Phosphoprotein and Abelson Interactor 1 in Human Platelets: A Concerted Computational and Experimental Approach

Abstract: Objective-The goal of this study was systematic profiling of vasodilator-stimulated phosphoprotein (VASP)-Ena/VASP homology 1 (EVH1) interactors in human platelets using a combined in silico and in vitro approach. Methods and Results-Exploiting the information of the comprehensive proteome catalogue in the PlateletWeb database (http://plateletweb.bioapps.biozentrum.uni-wuerzburg.de/PlateletWeb.php), we performed a motif search of all sequences and identified potential target sites of class I EVH1 domains in hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Gel-filtration analysis showed co-fractionation of VASP, c-Abl and Abi-1 at approximately 600 kDa. In addition to the previously identified EVH1 domain [48], we identified the CC domain of VASP as another binding site for Abi-1. The PP region of Abi-1 is critical for this interaction, which plays a crucial role in promoting phosphorylation of VASP by Abl.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Gel-filtration analysis showed co-fractionation of VASP, c-Abl and Abi-1 at approximately 600 kDa. In addition to the previously identified EVH1 domain [48], we identified the CC domain of VASP as another binding site for Abi-1. The PP region of Abi-1 is critical for this interaction, which plays a crucial role in promoting phosphorylation of VASP by Abl.…”
Section: Discussionmentioning
confidence: 75%
“…VASP localizes to focal adhesions and to the tips of lamellipodia and filopodia [21]. Others have also reported that VASP and Abi-1 partially co-localize at the tip of lamellipodia in human platelets when cells are stimulated with adenosine diphosphate or thrombin [48]. Therefore c-Abl translocates to the tip of lamellipodia, where VASP is enriched, with the help of Abi-1.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Therefore, we focused on VASP, a prominent PKA and PKG substrate and highly connected hub protein. Signal integration by VASP protein relies on the activation of the downstream cytoskeletal regulating signaling cascade [35,47]. Taking into account the two major known PKA/PKG phosphorylation sites, Ser157 and Ser239, we accurately predict and experimentally validate resulting differential activation in quantitative terms of specific PKA mediated phosphorylations on VASP.…”
Section: Discussionmentioning
confidence: 99%
“…For example, cPlateletWeb (http://plateletweb.bioapps.biozentrum.uni-wuerzburg.de) is an Internet-based platform organizing signaling network [59, 60]. A study based on PlateletWeb found a novel interaction between vasodilator-stimulated phosphoprotein and Abelson interactor 1 in human platelets [61]. Another database is Reactome (http://www.reactome.org), where extensive data have been collected, analyzed, and grouped in different pathways [62].…”
Section: Global Approaches In Studying Platelet–vessel Wall Interactionsmentioning
confidence: 99%